An Analysis of the Quality of the Central American Strategy for Rural Territorial Development (ECADERT) as a Regional Public Policy - Fernández Portillo, Luis Antonio; Universidad Loyola Andalucía (2015)
The Central American Strategy for Rural Territorial Development is a regional policy regarding the rural territorial development of the Central American Integration System. A group of stakeholders was interviewed in order to analyze whether its different stages have characteristics that support the implementation and achievement of its desired goals. The results indicate that the design of this policy shows positive characteristics regarding the participatory process that involves the major stakeholders. However, the situation is worse regarding the implementation, primarily because of its weak ties to integrate system institutions, lack of funding, and the low involvement of national governments.